2022
DOI: 10.1108/cms-05-2021-0195
|View full text |Cite
|
Sign up to set email alerts
|

The impact of project manager’s emotional intelligence on project performance: a meta-analysis

Abstract: Purpose A project manager’s (PM) emotional intelligence (EI) is essential for project performance (PP). However, the cause and effect and the potential moderators of the relationship between EI and PP remain disputed. Some scholars found a positive association between PMs’ EI and project outcomes, while some other studies showed non or negative relation. This paper aims to find the relationship between PMs’ EI and PP and the factors that influence this relationship based on diverse prior research. Design/met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 130 publications
0
4
0
Order By: Relevance
“…In recent years, authors such as Fareed et al [ 161 ], Zhang and Hao [ 162 ], and Zhang et al [ 163 ] have tackled this issue. More specifically, Fareed et al [ 161 ] point out that EI, project managers' intellectual competencies, and transformational leadership contribute significantly to project success.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In recent years, authors such as Fareed et al [ 161 ], Zhang and Hao [ 162 ], and Zhang et al [ 163 ] have tackled this issue. More specifically, Fareed et al [ 161 ] point out that EI, project managers' intellectual competencies, and transformational leadership contribute significantly to project success.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang and Hao [ 162 ] have determined that a project manager's EI influences the willingness to achieve objectives in a project; that is, it has a more effective influence on leading team members (mediating team cohesion and duration in project management). Zhang et al [ 163 ] investigated the factors influencing the relationship between project managers' EI and project performance, concluding that project managers' EI positively and significantly influences project performance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The coefficient of determination represents the relationship between dependent and independent variable. Analyzed value of R-Square is shown in Table 6, which provides insight of this relationship between dependent and independent variable either it is weak, moderate, or strong (Henseler et al, 2015), (Henseler et al, 2016) Based on the earlier research of Zhang, Hao, and Chung (2023), meta-analysis 5329 observation from independent research during 1990 to 2021 showed that there is positive association between emotional intelligence and project success. We also found, and the researchers argued that Project Managers with higher level of Emotional Intelligence develop a bond, a trust with his team which enables him to control the output of the workers.…”
Section: Coefficient Of Determination (R 2 )mentioning
confidence: 99%